2015
DOI: 10.1039/c5ce00960j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous and tetragonal zirconia with inherited morphology from metal–organic frameworks

Abstract: Controlled synthesis of porous metal oxides with desired morphology has been motivating scientists to explore and develop new preparation methodologies. Among them, thermal decomposition of metal-organic frameworks (MOFs) has been employed for the fabrication of several metal oxides. In this work, this strategy is employed to prepare mesoporous and tetragonal zirconia (t-ZrO2) from metal-organic framework (UiO-66), acting as both morphological template and zirconium source. This process avoids the use and remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…In the field of catalysis, the high accessibility of their metal nodes and their reactivity have started to be exploited as well, even if stability issues in the conditions of catalysis still often remain to be solved. Besides, the scope of MOF application was recently broadened by using these hybrid materials as sacrificial templates to synthesize either carbonaceous or purely inorganic materials with unique textural properties depending on the thermal treatment used for their transformation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of catalysis, the high accessibility of their metal nodes and their reactivity have started to be exploited as well, even if stability issues in the conditions of catalysis still often remain to be solved. Besides, the scope of MOF application was recently broadened by using these hybrid materials as sacrificial templates to synthesize either carbonaceous or purely inorganic materials with unique textural properties depending on the thermal treatment used for their transformation …”
Section: Introductionmentioning
confidence: 99%
“…Besides, the scope of MOF application was recently broadened by using these hybrid materials as sacrificial templates to synthesize either carbonaceous or purely inorganic materials with unique textural properties depending on the thermal treatment used for their transformation. [35][36][37][38] In this contribution, the selected MOF is an aluminum-based MIL-53(Al) composed of aluminum hydroxyl chains connected by terephthalate organic linkers and running along one-dimensional channels. It gathers the attributes required to obtain a porous nickel-alumina solid solution after its calcination: on one hand, it possesses a high porosity and metal-cluster accessibility expected to favor the homogeneous dispersion of nickel species within the oxide structure; on the other hand, it contains organics whose decomposition enables the formation of porosity in the obtained alumina.…”
Section: Introductionmentioning
confidence: 99%
“…6 In contrast, Inoue et al and Kil et al reported the synthesis of tetragonal zirconia nanoparticles by a glycothermal method. 7,8 Furthermore, the sol-gel method, [9][10][11][12][13] precipitation method using various agents, [14][15][16][17] high temperature hydrolysis method, 18,19 thermal decomposition process of metal-organic frameworks (MOFs), 20 hydrothermal method using various template agents, 21 oil/water interface (emersion) method, 22 and aqueous gelation method 14,23 have been reported for the synthesis of the metastable tetragonal zirconia nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nanoscale pores in metal oxide such as zirconium oxide nanoparticles play a vital role to enhance the physical and chemical reactivity of nanoparticles and promising potential applications in adsorption, catalysis, gas purification, sensors as well as in biological application 1 2 3 . But, development of nanopores in zirconium oxide is a great challenge and numerous strategies have been devoted to synthesize nanoscale porous zirconium oxide 4 5 6 7 8 . Several synthesis approaches such as sol-gel 9 , precipitation 6 , tape casting 10 , oil emulsion method 11 and solvothermal 12 have been employed to develop porous zirconium oxide by using hard or soft templates as well as self-assembly process with the help of specific surfactants to meet the requirement for different applications 5 13 .…”
mentioning
confidence: 99%
“…But, development of nanopores in zirconium oxide is a great challenge and numerous strategies have been devoted to synthesize nanoscale porous zirconium oxide 4 5 6 7 8 . Several synthesis approaches such as sol-gel 9 , precipitation 6 , tape casting 10 , oil emulsion method 11 and solvothermal 12 have been employed to develop porous zirconium oxide by using hard or soft templates as well as self-assembly process with the help of specific surfactants to meet the requirement for different applications 5 13 . The approach using either templates or self-assembly process using surfactants (such as sodium dodecyl sulfate, ammonium lauryl sulfate, sodium lauryl sulfate) for developing porous materials needs complicated pre-preparation and or post-treating processes.…”
mentioning
confidence: 99%